Impact of traditional Chinese Baduanjin exercise on menstrual health among international female students studying in China: a randomized controlled trial - Alkhatib, Asem; Alshikh Ahmad, Hoda; Zhang, Ci; Peng, Wenwen; Li, Xianhong (Frontiers in Public Health, 2024)
Background Menstrual symptoms were the common complaints of international female students during the acculturation period, and the symptoms negatively affected the daily life and school performance of those women. The present study aimed to evaluate the effectiveness of the traditional Chinese Baduanjin exercise on reducing menstrual symptoms for international female students studying in China during the acculturation period. Methods We conducted a randomized controlled trial among 62 international female students who suffered menstrual symptoms during the first 6 months after arriving in China. The study was carried out at three campuses of the two largest universities in the capital of a province in south-central China from March to October 2021. After screening, participants were randomly assigned to a control or intervention group. The intervention group engaged in 24 weeks of Baduanjin exercise for at least 30 min per day. The menstrual symptoms, sociocultural adaptation, perceived stress, and sleep quality were evaluated at baseline, the 12th week, and the 24th week. The chi-square test or Fisher's exact test, paired sample t-test, and multivariate analysis of variance (MANOVA)were adopted to analyze the data using SPSS 25.0. Results Totally, 62 participants were enrolled in this study from 30 countries. Their mean age was 27.87 ± 5.58 years. None of the participants reported an adverse event. The results of the MANOVA test showed that the traditional Chinese Baduanjin exercise reduced the total score of MSQ among international female students (intervention: 47.83 ± 8.71 vs. control: 65.12 ± 16.86; F = 19.49, P < 0.01). In addition, the results of the MANOVA indicated statistically significant decreases in scores for the two subscales of MSQ: premenstrual symptoms (intervention: 17.07 ± 3.33 vs. control: 28.42 ± 7.56; F = 44.70, P < 0.01)and menstrual pain (16.03 ± 4.53 vs. 19.58 ± 5.14; F = 6.50, P < 0.05). Moreover, the results showed that traditional Chinese Baduanjin exercise reduced the scores of the sociocultural adaptation level, the perceived stress level, and sleep quality and improved the blood progesterone hormone and blood estrogen hormone. Conclusion Regular Baduanjin exercise is a safe, acceptable, and effective form of exercise to promote international female students' menstrual health, reduce stress levels, and improve sleep quality. Trial registration www.chictr.org.cn, Chinese Clinical Trial Registry: ChiCTR2300072376.